Hubungan Kebiasaan Konsumsi Makanan Cepat Saji Dan Status Gizi Dengan Kejadian Gastritis Pada Siswa-Siswi Jurusan DKV Kelas X 1 Dan X2 Di SMK Negeri 1 Luragung Kabupaten Kuningan Tahun 2025: The Relationship Between Fast Food Consumption Habits and Nutritional Status with the Incidence of Gastritis Among 11th Grade DKV Students at SMK Negeri 1 Luragung, Kuningan Regency, in 2025 - Prawira Negara, Muhamad Ihksan; Drajat, Dito; Rizqi, Alfiani (Universitas Pahlawan Tuanku Tambusai, 2025)
Consumption habits have an important and influential role in individual well-being. Food consumptionhabits include the frequency of meals, the type of food consumed, and the portion and timing ofmeals. An unhealthy diet can contribute to an increase in obesity and other chronic diseases.Nutritional status is a person's physical condition and status that is affected by the intake of foodconsumed. Nutritional status includes such as weight and height. Gastritis is one of the healthproblems that often occur in adolescents and can be influenced by various factors, including fast foodconsumption habits and nutritional status. This study aims to find out whether there is a relationshipbetween fast food consumption habits and nutritional status with the incidence of gastritis in studentsof DKV X1 and X2 classes at SMK Negeri 1 Luragung, Kuningan Regency. The method used wasquantitative with a descriptive correlation design and a cross-sectional approach, involving 68respondents. The results showed that there was no significant relationship between fast foodconsumption (p=0.782) (< 0.05), and nutritional status (p=0.951) (< 0.05), and the incidence of gastritis.The majority of respondents ate fast food frequently (83.0%) and had good nutritional status (56.2%).The incidence of gastritis was found in 10.3% of respondents. In conclusion, fast food consumption andnutritional status were not directly related to gastritis in adolescents in grades X1 and X2 DKV SMKNegeri 1 Luragung were assigned with values of (p=0.782) (< 0.05) in fast food habits and (p=0.951) (<0.05) in nutritional status.